Netiquette of Gen Z Students: A Phenomenological Study of Gen Z Students in the 4.0 Era of the University Of Mataram - Nurul Atiba; Ernawati; Rani Ayu Ningtias; Idayanti; Ahda Rizkiani; Ainun Hidayah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research explores the understanding and application of netiquette among Gen Z students at Mataram University. In the 4.0 digital era, it is important for the younger generation to understand online communication ethics. Using a phenomenological approach, this research identifies students' experiences related to netiquette and the challenges they face. The results show that students are aware of the importance of digital ethics, but many are not familiar with the term netiquette. The lack of socialization and formal education is the main factor behind this lack of understanding. This research aims to contribute to the development of a more structured digital literacy program, so that students are expected to interact positively and productively in the online world.